Development of financial intermediation and the dynamics of rural-urban inequality: China, 1978 - 98 - Yiu Por Chen; Mingxing Liu; Qi Zhang (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2006)
Using China as a test case, this paper empirically investigates how the development of financial intermediation affects rural-urban income disparity (RUID). Using 20-year province level panel data, we find that the level of financial development is positively correlated with RUID. Examining two subperiods, 1978-88 and 1989-98, we test several competing hypotheses that may affect RUID. We find that the increase of RUID may be explained by fiscal policy during the first period and financial intermediates during the second period. In addition, we show that the direction of the Kuznets effect on RUID is sensitive to changes in government development policies. The rural development policies during the first period may have enhanced the rural development and reduced RUID. However, the financial intermediary policy during the second period focused on urban development and increased both urban growth and intra-urban inequalities, thus leading to an increase in RUID. Finally, we show that RUID is insensitive to the provincial industrial structure (the share of primary industry in GDP). These results are consistent with the traditional urban-bias hypothesis and are robust to the inclusion of controls for endogeneity issues. This study adds to the economic inequality literature by clarifying the effects of government policies on the underlying dynamics on convergent and divergent effects on rural-urban inequality. – housing ; transportation ; planning ; coordination ; reform ; equity ; justice ; inequality ; central banks ; China
Keywords: G28; P21; P25; P34; D63; E58; 330; Finanzintermediär; Regionale Einkommensverteilung; Stadt-Land-Beziehung; China